Evaluation of antimicrobial and sporicidal activity of hypochlorous acid against clinical isolates from diabetic foot gangrene patients - Mahdi, M. A.; Abbas, M. A.; Khlaif, M. M. (Regulatory Mechanisms in Biosystems, 2026)
Diabetic foot ulcers and gangrene, often infected with multidrug-resistant pathogens and resilient bacterial spores, require effective topical antisepsis to prevent systemic infection and promote healing. This study compared the concentration- and time-dependent bactericidal and sporicidal activity of four common disinfectants against clinical isolates from diabetic foot infections. Forty-five clinical swab samples were collected from DFU patients at Baghdad Teaching Hospi t al. Pathogens were isolated and identified using the Vitek 2 Compact system. Quantitative time-kill assays and dilution-neutralization methods were employed to determine the log 10 reduction of vegetative bacteria against different type s of disinfectant and exposure times (1 to 30 minutes). S taphylococcus aureus was the most frequent isolate (40.8%), next to P seudomonas aeruginosa (24.5%) and Acinetobacter baumannii (20.4%). The time-kill study revealed that HOCl (200 ppm) was the most effective and acted the fastest to kill S. aureus , achieving a 6.94 ± 0.71 log 10 reduction of bacteria within 1 minute Moreover, HOCl also proved high ly effective in kill ing bacteria spores, achieving a 7.87 ± 0.76 log 10 reduction in C lostridium perfringens spores in 20 minutes. NaOCl (0.05%) showed high bactericidal activity with a 7.60 ± 1.19 log 10 reduction against S. aureus but with a long exposure time. HOCl 200 ppm showed rapid bactericidal and sporicidal activity against diabetic foot pathogens, which makes it an effective yet safe clinical-grade wound disinfectant.